Sorting signals in the MHC class II invariant chain cytoplasmic tail and transmembrane region determine trafficking to an endocytic processing compartment. - Odorizzi, C; Trowbridge, I; Xue, L; Hopkins, C; Davis, C; Collawn, J (1994)
Targeting of MHC class II molecules to the endocytic compartment where they encounter processed antigen is determined by the invariant chain (Ii). By analysis of Ii-transferrin receptor (TR) chimera trafficking, we have identified sorting signals in the Ii cytoplasmic tail and transmembrane region that mediate this process. Two non-tyrosine-based sorting signals in the Ii cytoplasmic tail were identified that mediate localization to plasma membrane clathrin-coated pits and promote rapid endocytosis. Leu7 and Ile8 were required for the activity of the signal most distal to the cell membrane whereas Pro15 Met16 Leu17 were important for the membrane-proximal signal. The same or overlapping non-tyrosine-based sorting signals are essential for delivery of Ii-TR chimeras, either by an intracellular route or via the plasma membrane, to an endocytic compartment where they are rapidly degraded. The Ii transmembrane region is also required for efficient delivery to this endocytic processing compartment and contains a signal distinct from the Ii cytoplasmic tail. More than 80% of the Ii-TR chimera containing the Ii cytoplasmic tail and transmembrane region is delivered directly to the endocytic pathway by an intracellular route, implying that the Ii sorting signals are efficiently recognized by sorting machinery located in the trans-Golgi.